Characterization of municipal sludge using oxygen utilization rate (OUR) model/ Zurhaida Azlan - Azlan, Zurhaida (2007)
Characterization of sludge is the first step in designing the process for sludge treatment. At present, the sludge characteristic in Malaysia is based on bulk parameters such as Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD) that indicate the concentration of organic matter and the total amount of biodegradable organic matter respectively. Unfortunately, their relevance in explaining microbial process during treatment had been questioned. More focus is needed on the biomass present in the sludge as this is the active component directly influencing the biodegradation processes. This proposal outlines an alternative method to characterise the municipal sludge by means of respirometric method. Characterization of sludge is done by evaluating the rate degradation of organic compound indirectly. This evaluation can be done by respirometry technique approach - based on its Oxygen Utilization Rate (OUR). At the end of this research, the sludge characterization will be in the form of COD-fractions, which includes the amount of the active biomass.